MENINGKATKAN KETERAMPILAN BERPIKIR KRITIS MENGGUNAKAN SMART MODEL UNTUK SISWA SEKOLAH DASAR - Noorhapizah Noorhapizah; Diani Ayu Pratiwi; Karmilla Ramadhanty (Bajang Institute, 2022)
The purpose of the study was to determine teacher activities, student activities, critical thinking, and student learning outcomes after learning was carried out using the RESEARCH learning model. The subjects of the research were the 12th graders of SDN Pantai Hambawang Barito Kuala. The method used is a qualitative and quantitative approach with the type of Classroom Action Research. Qualitative data obtained from observation of activities, student activities, and critical thinking skills. Quantitative data obtained from learning outcomes, critical thinking activities, collaboration and student independence. This activity lasted for 4 meetings, with the results of the teacher's activity reaching a score of 30 with very good criteria. Observation of student activity reached a percentage of 83% with very active criteria. Students' critical thinking skills reach a percentage of 91% with very skilled criteria. Cognitive learning outcomes reached 100% (classical). Based on this research, the SMART model can increase teacher activity, activity, critical thinking, and student learning outcomes.